Predicting Fear of Emotional Intimacy Based on Childhood Trauma: The Mediating Role of Interpersonal Emotion Regulation Among Student Couples - Moharrami Ghidari , Fariba; Asadolah Tooyserkani, Maryam (KMAN Counseling & Psychology Nexus, 2027)
The present study aimed to predict fear of emotional intimacy based on childhood trauma, with the mediating role of interpersonal emotion regulation among student couples. In terms of purpose, this research was applied in nature. Regarding methodology, it was a quantitative, descriptive-correlational study utilizing path analysis. For this purpose, 250 student couples from branches of the Islamic Azad University in Tehran were selected through convenience random sampling. Participants completed the Childhood Trauma Questionnaire (CTQ; Bernstein et al., 2003), the Fear of Intimacy Scale (Descutner & Thelen, 1991), and the Interpersonal Emotion Regulation Questionnaire (IERQ; Hofmann et al., 2016). Data were analyzed using SPSS version 27 and AMOS through path analysis. The findings indicated that childhood trauma was a significant predictor of fear of emotional intimacy in couples’ relationships. Furthermore, interpersonal emotion regulation played a significant mediating role in the relationship between childhood trauma and fear of emotional intimacy. In other words, experiences of early-life trauma may influence individuals’ fear of emotional closeness in romantic relationships by weakening their ability to regulate emotions within interpersonal interactions. The results highlight the importance of addressing early life experiences and strengthening emotion regulation skills to improve the quality of couples’ relationships, particularly during the university years. Accordingly, counseling and therapeutic interventions focused on enhancing interpersonal emotion regulation may be effective in reducing fear of intimacy and promoting marital satisfaction.